Recurrent Catastrophic Ceramic Femoral Head Failure in Total Hip Arthroplasty - S. M. M. Tai; L. Parker; N. J. de Roeck; J. A. Skinner (Case Reports in Orthopedics)
Fracture of a modern ceramic head component in total hip replacement is an uncommon but catastrophic complication. Hence, the occurrence of a second ceramic head fracture in the same hip replacement of an individual represents a perishingly rare event. We present the case as a means of highlighting potential risk factors for ceramic head fracture and suggest possible management strategies in such cases.